Is bureaucracy being busted in research ethics and governance for health services research in the UK? Experiences and perspectives reported by stakeholders through an online survey - Snooks, Helen; Khanom, Ashrafunnesa; Ballo, Rokia; Bower, Peter; Checkland, Katherine; Ellins, Jo; Ford, Gary A; Locock, Louise; Walshe, Kieran (BMC public health, 2023)
Background It has long been noted that the chain from identification of need (research gap) to impact in the real world is both long and tortuous. This study aimed to contribute evidence about research ethics and governance arrangements and processes in the UK with a focus on: what works well; problems; impacts on delivery; and potential improvements. Methods Online questionnaire widely distributed 20th May 2021, with request to forward to other interested parties. The survey closed on 18th June 2021. Questionnaire included closed and open questions related to demographics, role, study objectives. Results Responses were received from 252 respondents, 68% based in universities 25% in the NHS. Research methods used by respondents included interviews/focus groups (64%); surveys/questionnaires (63%); and experimental/quasi experimental (57%). Respondents reported that participants in the research they conducted most commonly included: patients (91%); NHS staff (64%) and public (50%). Aspects of research ethics and governance reported to work well were: online centralised systems; confidence in rigorous, respected systems; and helpful staff. Problems with workload, frustration and delays were reported, related to overly bureaucratic, unclear, repetitive, inflexible and inconsistent processes. Disproportionality of requirements for low-risk studies was raised across all areas, with systems reported to be risk averse, defensive and taking little account of the risks associated with delaying or deterring research. Some requirements were reported to have unintended effects on inclusion and diversity, particularly impacting Patient and Public Involvement (PPI) and engagement processes. Existing processes and requirements were reported to cause stress and demoralisation, particularly as many researchers are employed on fixed term contracts. High negative impacts on research delivery were reported, in terms of timescales for completing studies, discouraging research particularly for clinicians and students, quality of outputs and costs. Suggested improvements related to system level changes / overall approach and specific refinements to existing processes. Conclusions Consultation with those involved in Health Services Research in the UK revealed a picture of overwhelming and increasing bureaucracy, delays, costs and demoralisation related to gaining the approvals necessary to conduct research in the NHS. Suggestions for improvement across all three areas focused on reducing duplication and unnecessary paperwork/form filling and reaching a better balance between risks of harm through research and harms which occur because research to inform practice is delayed or deterred.